The Role And Position Of Basyarnas In The Settlement Of Islamic Banking Disputes - Moetaba, Ahmad (Fakultas Hukum, Universitas Islam Bandung, 2023)
In Islamic banking disputes, the institution authorized to resolve disputes is the Religious Court which is the litigation route, while there are several non-litigation routes such as deliberation, mediation, and sharia arbitration. The purpose of this study is to analyze the position of Basyarnas in resolving Islamic banking disputes. The research method uses a juridical approach that uses secondary data in the form of books, journals and laws and regulations that are analyzed qualitatively. The National Sharia Arbitration Board (Basyarnas) is an arbitration institution based on Islamic law. The National Sharia Arbitration Board was established by the Indonesian Ulema Council. The reason for the establishment of the National Sharia Arbitration Board is the idea of Sharia Economics which is characterized by the development of Islamic banking, with the example of the birth of Islamic banks which of course have disputes that must be resolved with sharia, for this reason the need to include other parties for mediation in resolving sharia disputes.